E-selectin is associated with stable angina and myocardial infarction in a sample of Kurdish population: 7170G>C and stable angina and myocardial infarction - Qasim Rahman, Lajan; Muhammad Ghareeb, Ruqaya (Cellular and Molecular Biology, 2024)
Endothelial dysfunction is the main factor that causes the onset of CAD. Leukocyte adhesion to the endothelium of the active blood artery wall has been demonstrated to be one of the early indicators of arteriosclerosis. This process is regulated by selectins. The purpose of this study is to ascertain the relationship between the polymorphisms in the E-selectin gene that have been linked to ischemic heart disease. We looked at the functional impact of the E-selectin gene polymorphism 7170G>C in Iraqi patients with IHD. This study was conducted on 200 participants who were admitted to the surgical specialty hospital-cardiac center in Erbil City, Iraq between October 2021 and May 2022. Based on the outcomes of the clinical examination, laboratory tests, coronary angiography (COA), acute myocardial infarction (MI) type ST-elevation myocardial infarction (STEMI), stable angina pectoris (SAP), and healthy control groups were tested. Each sample was subjected to Sanger sequencing. The polymorphism was significantly linked to stable angina and myocardial infarction Genotype CC was higher in SAP when compared with MI and control groups which was statistically significant with (p-value<0.05). A higher proportion of C allele was observed in SAP patients (15.7%) which was significantly higher than MI (14.58%) and control (10.8%). The statistical chi-square analysis for allele G frequency showed insignificant differences (p-value>0.05) between patients and the control group. Genetic variation in E-selectin such as polymorphism in nucleotide 7170 G>C at exon 4 region can significantly affect the outcome of cardiovascular diseases.